Zapisz w prostszej postaci
a) 3x + 4x +5y - 2y =
b) 2a - 3a + 7 - 6 =
c) 2x - 5x + 7 - x =
d) 2a + b - 4b =
e) x - 2x + 3 + x - 4 =
f) 3x - y + 4x - 2y =
g) 2x - 6 + 4x + 2 =
h) 3y - 5 - 5y - 6 =
i) -2a + 2b - 3a - 3b =
j) 1:2t - 2x + 3t - x - t =

( ps: 1:2 to znaczy jedna druga t , bo nie wiedzialem jak to napisać )

2

Odpowiedzi

2010-03-16T16:12:58+01:00
A) 3x + 4x +5y - 2y =7x+3y
b) 2a - 3a + 7 - 6 =-a+1
c) 2x - 5x + 7 - x =-4x+7
d) 2a + b - 4b =2a-3b
e) x - 2x + 3 + x - 4 =-1
f) 3x - y + 4x - 2y =7x-3y
g) 2x - 6 + 4x + 2 =6x-4
h) 3y - 5 - 5y - 6 =-2y-11
i) -2a + 2b - 3a - 3b =-5a-b
j) 1:2t - 2x + 3t - x - t = 2½t-3x
48 4 48
2010-03-16T16:14:02+01:00
A) 3x + 4x +5y - 2y = 7x+ 3y
b) 2a - 3a + 7 - 6 = a+1
c) 2x - 5x + 7 - x = -4x+ 7
d) 2a + b - 4b = 2a- 5b
e) x - 2x + 3 + x - 4 = 2x+3
f) 3x - y + 4x - 2y = -3y+7x
g) 2x - 6 + 4x + 2 =6x -4
h) 3y - 5 - 5y - 6 = -2y- 11
i) -2a + 2b - 3a - 3b = -5a-1b
j) 1:2t - 2x + 3t - x - t = 2 i 1:2t- 3x
17 3 17